An integrated DEM–FEM approach to study breakage in packing of glass cartridges on a conveyor belt - Boso, Daniela Paola; Braga, Tommaso; Ravasini, Simone; Škrbić, Tatjana; Puglisi, Andrea; Pinato, Odra; Chillon, Alberto; Frare, Maria Chiara; Giacometti, Achille (Granular matter, 2020)
The use of glass for pharmaceutical new applications such as high-technology drugs, requires the strictest container inertness. A common theme of paramount importance in glass container integrity preservation is the detailed mechanism driving the sudden failure due the crack propagation. Using a combination of discrete element method (DEM) and finite element method (FEM), a stress map for glass cartridges packed into an accumulation table and transported by a conveyor belt at a fixed velocity is obtained under realistic conditions. The DEM calculation provides a full description of the dynamics of the cartridges, as approximated by an equivalent sphere, as well as the statistics of the multiple collisions. The FEM calculation exploits this input to provide the maximum principal stress of different pairs as a function of time. Our analysis shows that, during their transportation on the conveyor belt, the cartridges are subject to several shocks of varying intensities. Under these conditions, a crack may originate inside the cartridge in the area of maximal tensile stress, and propagate outward. Estimated stresses are found in good agreement with real systems. Graphic abstract